Comparative study of neovascularization density in tracheal defect reconstruction with external oblique muscle aponeurosis patch and dry amniotic membrane (A study with New Zealand rabbits) - Afifudin, Muhammad; Wibodo, Marjono Dwi; Susilo, Dwi Hari (Edelweiss Applied Science and Technology, 2025)
The high incidence of complications makes tracheal defect reconstruction challenging to found the ideal technique to repair tracheal defect. The use of dry amniotic membrane to promoted wound healing processed and aponeurosis as a surgical patch and flap in reconstruction is not uncommon, but no studies had been conducted to analyze its combination uses in tracheal defect reconstruction, though its effectivity in wound healing was significant in reconstruction of other organs. This study aims to compare neovascularization in tracheal defect reconstruction using external oblique muscle aponeurosis patch only and using external oblique muscle aponeurosis patch combine with dry amniotic membrane patch. This randomized control trial is a laboratory experimental study using male New Zealand white rabbits. Randomization was carried out with permuted block randomization into a control group (reconstruction with external oblique muscle aponeurosis patch only) and a treatment group (reconstruction with external oblique muscle aponeurosis patch combine with dry amniotic membrane). Histopathological assessments were carried out 14 days after surgery. We got homogeneous samples in both groups (16 samples each) in terms of age (p=0.712), weight before procedure (p=0.247), and weight after procedure(p=0.534). Histopathological analysis showed that there were significant differences in neovascularization (p=0.007) between the two groups. It can be concluded that there are significant differences in neovascularization in New Zealand rabbits with tracheal defect using external oblique muscle aponeurosis patch only and external oblique muscle aponeurosis patch combine with dry amniotic membrane patch.